(untitled) (Journal of Industrial and Mechanical Engineering, 2020)
Due to the degradation of machinery and equipment materials, as well as the infrastructure in general, in whose design, construction and use engineers are permanently immersed, various types of corrosion are investigated, in real cases. The selection of cases directly affecting the aforementioned infrastructure was carried out through results of failure inspection activities in housing structures, applied research, deterioration of specific fluid conduction and storage systems, among others, supported by the application of metallography and non-destructive testing. Based on the above, a technical scientific analysis of various corrosion cases is made, through their metallurgical characteristics and some forms of prevention are noted, since this phenomenon contributes to the deterioration of metal systems, impoverishing the concept of environmental sustainability and increasing the operational cost of the infrastructure.